Chinese expert consensus on minimally invasive interventional treatment of trigeminal neuralgia - Fan, Xiaochong; Fu, Zhijian; Ma, Ke; Tao, Wei; Huang, Bing; Guo, Gang; Huang, Dong; Liu, Guangzhao; Song, Wenge; Song, Tao; Xiao, Lizu; Xia, Lingjie; et al. (Frontiers in Molecular Neuroscience, 2022)
Background and purpose Trigeminal neuralgia is a common condition that is associated with severe pain, which seriously affects the quality of life of patients. When the efficacy of drugs is not satisfactory or adverse drug reactions cannot be tolerated, minimally invasive interventional therapy has become an important treatment because of its simple operation, low risk, high repeatability and low cost. In recent years, minimally invasive interventional treatments, such as radiofrequency thermocoagulation (RF) of the trigeminal nerve and percutaneous microcompression (PMC), have been widely used in the clinic to relieve severe pain in many patients, however, some related problems remain to be addressed. The Pain Association of the Chinese Medical Association organizes and compiles the consensus of Chinese experts to standardize the development of minimally invasive interventional treatment of trigeminal neuralgia to provide a basis for its clinical promotion and application. Materials and methods The Pain Association of the Chinese Medical Association organizes the Chinese experts to compile a consensus. With reference to the evidence-based medicine (OCEBM) system and the actual situation of the profession, the Consensus Development Committee adopts the nominal group method to adjust the recommended level. Results Precise imaging positioning and guidance are the keys to ensuring the efficacy and safety of the procedures. RF and PMC are the most widely performed and effective treatments among minimally invasive interventional treatments for trigeminal neuralgia. Conclusions The pain degree of trigeminal neuralgia is severe, and a variety of minimally invasive intervention methods can effectively improve symptoms. Radiofrequency and percutaneous microcompression may be the first choice for minimally invasive interventional therapy.